2014
DOI: 10.2134/jeq2014.03.0108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acidifying Pig Diets on Emissions of Ammonia, Methane, and Sulfur from Slurry during Storage

Abstract: Ammonia (NH 3 ) volatilization from intensive livestock production is a threat to natural ecosystems. This study investigated pig diet manipulation by 1% (w/w) benzoic acid (BA) amendment and lowering of dietary electrolyte balance through substituting 1.4% (w/w) CaCO 3 with 2.0% (w/w) CaCl 2 . Urine and feces were collected separately from 24 pigs fed one of four diets (Control, +BA, +CaCl 2 , +BA+CaCl 2 ) in metabolic cages and mixed as slurry. During 103 d of storage, all acidifying diets consistently reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…The slurry pH of dairy cow [24] and pig slurry [42] was reported to be significantly correlated with VFA/NH 4 + +NH 3 . Eriksen et al [52] demonstrated that an increase in pH value during the first week of storage was caused by the mineralization of organically bounded N [53]. This pH increase could only be observed for the very fresh sow slurry (cold: +0.33 and warm: +0.08 pH units from week 0 to week 1) ( Figure 7, 'sow') because it still contains a high content of urea (see Section 4.3).…”
Section: Initial Ph Valuementioning
confidence: 99%
“…The slurry pH of dairy cow [24] and pig slurry [42] was reported to be significantly correlated with VFA/NH 4 + +NH 3 . Eriksen et al [52] demonstrated that an increase in pH value during the first week of storage was caused by the mineralization of organically bounded N [53]. This pH increase could only be observed for the very fresh sow slurry (cold: +0.33 and warm: +0.08 pH units from week 0 to week 1) ( Figure 7, 'sow') because it still contains a high content of urea (see Section 4.3).…”
Section: Initial Ph Valuementioning
confidence: 99%
“…To date, there is scarce literature (Petersen et al, 2013;Eriksen et al, 2014) regarding the use of slurries/urines with manipulated hippuric or benzoic acid content, and most of these have been conducted by increasing their concentration through direct T 1 1 1 1 1 1 1-1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 1-1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 addition of these compounds into the slurry (Fangueiro et al, 2015). However, this practice could be difficult to achieve due to the low solubility of both compounds (Krol et al, 2015).…”
Section: Diets and N 2 0 Emission In Soilmentioning
confidence: 99%
“…The use of sulphuric acid for acidification increases the concentration of inorganic sulphur in slurry, which may increase hydrogen sulphide emissions. Eriksen et al (2014), however, emphasize that low pH inhibits the growth and activity of microorganisms colonizing faeces, and thus reduces the amount of pollutants released.…”
Section: Methods For Reducing Emissions Of Gaseous Pollutantsmentioning
confidence: 99%